Antiproliferative glabretal-type triterpenoids from the root bark of Dictamnus dasycarpus. Issue 3 (1st February 2015) - Kim, Nahyun; Cho, Kyu-Won; Hong, Seong Su; Hwang, Bang Yeon; Chun, Taehoon; Lee, Dongho
Graphical abstract